Intracellularly Expressed Single-Domain Antibody against p15 Matrix Protein Prevents the Production of Porcine Retroviruses - Dekker, Sylvia (American Society for Microbiology, 2003)
The presence of porcine endogenous retroviruses presents a potential risk of transmission of infectious diseases (xenozoonosis) if tissues and organs from genetically modified pigs are to be used in xenotransplantation. Here, we report that intracellular expression of a llama single-domain antibody against p15, the matrix domain protein of the porcine endogenous retrovirus Gag polyprotein, blocks retrovirus production, providing the possibility of eliminating the risk of infection in xenotransplantation.